HADITH ON THE EXCELLENCE OF AL-FATIHAH: THE EXAMINATION OF ITS CHAIN OF TRANSMISSION - Amiruddin, Andi Muhammad Ali (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2021)
Hadith, as commonly defined by hadith scholars (al-muhddithun), is a record of the Prophet’s sayings, deeds and tacit approval. Even it may include the description of the Prophet’s features and physical appearance. Hadith contains details of faith and doctrine, ritual issues, ethics and many others which are related with the contents of the Quran and on the Quranic verses as well. This article is aimed at assessing the validity of a hadith on the excellence of al-Fatihah, the opening chapter of the Quran. In doing so, this article presents the chain of transmission of the hadith by assessing the details of all persons involved in relating the hadith. It is found the hadith assessed is reliable and may be relevant for Muslims to use as a source for their religious activities.